PENTINGNYA RUMAH POTONG AYAM HALAL - Agus Kholili; Dadang Ibnu; Evie Indriani; Nur Solihat (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Sunan Gunung Djati Bandung, 2021)
With the increase in consumption of chicken meat on the market, followed by the development of a chicken slaughterhouse business. The current problem is the halal in slaughtering chickens which is still doubtful halal. The way to slaughter that happens a lot in the market needs to get the attention of the authorities, such as LPPOM MUI. The level of concern of broiler sellers causes the quality of broiler to be low. Starting from cutting that is not in accordance with Islamic law, the circulation of tiren chicken (died yesterday) which will be a long list of the need for research on chicken products. The process of slaughtering which is not in accordance with Islamic law has the potential risk of decreasing the quality of the product and the risk of being illicit because initially the product has a halal status will be haram if there are other substances that are forbidden to mix with halal essence. The benefit to be taken is the creation of consumer loyalty to cut chicken products that have a clear method of cutting. Therefore the purpose of this paper is to find out the concept of cutting chicken in accordance with the Shari'a.Keyword: chicken slaughterhouse, halal